Autotoxin affects the rhizosphere microbial community structure by influencing the secretory characteristics of grapevine roots - Liu, Qianwen; Zhang, Liheng; Wang, Lu; Wu, Qingchun; Li, Kun; Guo, Xiuwu (Frontiers in Microbiology, 2022)
Autotoxins secreted by roots into the soil can trigger rhizosphere microecological imbalances and affect root secretory properties resulting in conditions such as replanting disease. However, information on the effect of autotoxins on root secretion characteristics and regulation of the composition of rhizosphere microorganisms by altered root exudates is limited. In this study, autotoxin ρ-hydroxybenzoic acid (4-HBA) was added to the soil of potted grapevine seedlings, CO2 pulse-labeling and DNA stable isotope probing were used to track the rhizosphere microbiome that assimilates root exudates. Bacterial and fungal microbiomes that assimilated plant-derived carbon were identified by high-throughput sequencing. Results showed that 4-HBA treatment altered bacterial and fungal communities in 13C-labeled organisms, with a lower abundance of beneficial bacteria (e.g. Gemmatimonas, Streptomyces and Bacillus) and a higher abundance of potential pathogen fungi (e.g. Fusarium, Neocosmospora, Gibberella and Fusicolla) by changing the composition of root exudates. The exogenous addition of upregulated compound mixtures of root exudates reduced the abundance of beneficial bacterial Bacillus and increased the abundance of potential pathogen fungi Gibberella. These results suggest that 4-HBA can alter root secretion properties and altered root exudates may enrich certain potential pathogens and reduce certain beneficial bacteria, thereby unbalancing the structure of the rhizosphere microbial community.